Characterization of caspases in the apoptotic pathway of Aedes aegypti - Bhandary, Binny (Kansas State University, 2016)
Caspases are a conserved family of cysteine proteases that play important roles in apoptosis and innate immunity as well as other cellular processes. Eleven caspase genes have been annotated in the mosquito Aedes aegypti. Amongst these, previous studies have demonstrated functional roles for AeDronc, CASPS7 and CASPS8 in the Ae. aegypti apoptosis pathway, while CASPS18 and CASPS19 have also been functionally characterized. A previous study from our research group showed that AeIAP1 has preferential binding for CASPS7 compared to CASPS8. In this study, it was confirmed that AeIAP1 has a higher capacity to inhibit CASPS7 than CASPS8. Furthermore, five of the remaining Ae. aegypti caspases, namely CASPS15, CASPS16, CASPS17, CASPS20 and CASPS21, were characterized. An attempt was made to classify these caspases as initiator or effector caspases, based on factors such as the length of their prodomain, sequence similarity to known Drosophila initiator and effector caspases, and their substrate specificity. The functions of these caspases in apoptosis was examined in the Ae. aegypti cell line Aag2, by using RNA interference to reduce their expression and test the effect on apoptosis. Recombinant CASPS16, 17, 20 and 21 were produced in bacteria and the abilities of these recombinant proteins to cleave different caspase substrates were examined. From the resulting data, it was concluded that CASPS17 and CASPS21 are likely to be effector caspases since they preferred a effector caspase substrate. When considering the prodomain length, CASPS17 has a short prodomain, but CASPS21 has a long prodomain, which is normally associated with initiator caspases. CASPS20 did not show preference for any specific substrate and has a short prodomain. Since it did not have a specific preference of substrate, it is likely to be an effector caspase based on prodomain length. CASPS16 showed a slightly higher preference for the initiator caspase substrate WEHD, and has a long prodomain. Based on these results, CASPS16 is likely an initiator caspase. To examine the potential roles of CASPS15, 16, 17, 20 and 21 in apoptosis, their expression in Aag2 cells was knocked down using RNA interference. Successful knockdown was verified by qRT-PCR. After silencing specific caspases, the cells were exposed to two different apoptotic stimuli, ultraviolet radiation (UV) or the RNA synthesis inhibitor actinomycin D (ActD). Following apoptotic treatment, apoptosis was measured by two methods; caspase activity was measured using an effector caspase substrate, and phosphatidyl serine exposure on the outer leaflet of the plasma membrane, which occurs in apoptotic cells, was measured by Annexin V staining and flow cytometry. In cells where CASPS15, 16, 17, 20 or 21 had been knocked down and the cells were then treated with UV or ActD, it was observed that effector caspase activity and Annexin V staining were both significantly lower than in UV- or ActD-treated cells that had received control double-stranded RNA. Together these results suggest that all of these caspases are involved in apoptosis in Aag2 cells. This study serves as a starting point for further research on Ae. aegypti caspases and their roles in specific cellular processes.
Keywords: Apoptosis; Caspase; Aedes aegypti; Caspase activity